The London Midland & Scottish Railway : A Century and a Half of Progress ; LMS 150 - Whitehouse, Patrick and Thomas, David St John (UK David and Charles, 1998)
This text celebrates 150 years of the London Midland and Scottish Railway retelling in words and pictures the full story, from the earliest beginnings with the opening of the London and Birmingham line through the problem-ridden years following the amalgamation in 1923 to 1998.
Include Illustration and Index
Keywords: London, Midland and Scottish Railway Company -- Railroads -- Great Britain